2021
DOI: 10.1001/jamapediatrics.2020.3220
|View full text |Cite
|
Sign up to set email alerts
|

Equity Is the Foundation of Adolescent-Friendly Health Care

Abstract: Two recent reports, The Promise of Adolescence:Realizing Opportunity for All Youth (Promise) 1 and Promoting Positive Adolescent Health Behaviors and Outcomes: Thriving in the 21st Century (Promoting), 2 from the National Academies of Sciences, Engineering, and Medicine (National Academies) conclude that adolescence is a developmental period full of opportunity for extraordinary learning and growth. The dramatic plasticity and malleability during this period prime adolescents to explore new environments, pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…A cancer diagnosis is a critical event that threatens an individual and interferes with all the domains around which their life revolves: physical, psycho-emotional and relational [4,25,26]. Recently, the European Commission of the EU launched the childhood cancers and cancers in adolescents and young adults initiative to increase understanding of pediatric and AYA cancer [27,28]. This contribution has observed the weight of some possible complementary care actions to the medical aspect [3][4][5]12,28,29] that, specifically, healthcare staff wanted to investigate and understand: (1) care of communication between doctor and patient is an access key that lays the foundation for a functional relationship between the parties that is useful for compliance and adherence to treatments [3,[8][9][10][11]; (2) attention to thoughts, fears and changes in self-perception guarantees a greater understanding of the impact of the side effects of the medical procedures, as well as of the behavioral reactions of the patients [3,9,10,12,25]; (3) adequate consideration of the presence of other individuals involved in the treatment process can help the staff manage the simple or complicated sequelae of treatments, and favors the continuation of normality for each patient, offering a positive psychological impact [3,6,[9][10][11][12]25]; (4) subjective ways in which each patient copes with the disease and its treatments allows each operator to understand and refrain from judging these actions, both in the present and in the planning sense [3][4][5]7,9,10,25,26,…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A cancer diagnosis is a critical event that threatens an individual and interferes with all the domains around which their life revolves: physical, psycho-emotional and relational [4,25,26]. Recently, the European Commission of the EU launched the childhood cancers and cancers in adolescents and young adults initiative to increase understanding of pediatric and AYA cancer [27,28]. This contribution has observed the weight of some possible complementary care actions to the medical aspect [3][4][5]12,28,29] that, specifically, healthcare staff wanted to investigate and understand: (1) care of communication between doctor and patient is an access key that lays the foundation for a functional relationship between the parties that is useful for compliance and adherence to treatments [3,[8][9][10][11]; (2) attention to thoughts, fears and changes in self-perception guarantees a greater understanding of the impact of the side effects of the medical procedures, as well as of the behavioral reactions of the patients [3,9,10,12,25]; (3) adequate consideration of the presence of other individuals involved in the treatment process can help the staff manage the simple or complicated sequelae of treatments, and favors the continuation of normality for each patient, offering a positive psychological impact [3,6,[9][10][11][12]25]; (4) subjective ways in which each patient copes with the disease and its treatments allows each operator to understand and refrain from judging these actions, both in the present and in the planning sense [3][4][5]7,9,10,25,26,…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the US National Academies' reports emphasize that practices for adolescents should create incentives for discovery and innovation. Its review, "Promoting Positive Adolescent Health Behaviors and Outcomes", found that programs teaching social and emotional skills-including self-awareness, self-management, social awareness, relationship skills, and responsible decision-making-may be particularly successful in promoting positive youth development [5,9,10,13,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…More than ever, it is essential for health care professionals to understand the impact of the social determinants in the lives of youth including in their health. This impact often leads to the health inequities often observed based on race, class, gender, gender identity and sexual orientation ( 42 ). Clinicians need to consistently provide a patient-centered approach, culturally aware and sensitive care, and screen regularly for social determinants, health, mental health conditions and safety ( 43 ), and to adopt active anti-racist practices including pushing back against institutional forms of racism.…”
Section: Discussionmentioning
confidence: 99%
“…Equity was one of the stated goals of our institution and achieving equity has long been recognized as a key objective in resource allocation and prioritization ethics. There is growing support for the idea that healthcare systems have positive obligations to not just deliver healthcare equally, but to actively promote health equity, both domestically (27)(28)(29)(30) and globally (31,32). The responsibility to work towards equity by identifying, addressing, and actively combating health inequities now within the healthcare system became undeniably clear over the course of 2020 and 2021 (32)(33)(34)(35)(36).…”
Section: Exploring the Substantive Ethics Principles Equitymentioning
confidence: 99%